Integration of Industry 5.0 Principles in Sustainable Manufacturing Systems: A Literature Review on the Role of Human–Machine Collaboration and Its Impact on Productivity - Purnomo, Rahmat; Wedono, Bramono Wangsa (Journal of Renewable Engineering, 2026)
The transition from Industry 4.0 to Industry 5.0 represents a paradigm shift from technology-driven efficiency toward human-centric, sustainable, and resilient manufacturing systems. Human–machine collaboration is increasingly recognized as a core mechanism for achieving productivity while simultaneously addressing social and environmental objectives. This study aims to systematically review the integration of Industry 5.0 principles in sustainable manufacturing, with particular emphasis on the role of human–machine collaboration and its impact on productivity. A Systematic Literature Review (SLR) was conducted using peer-reviewed journal articles published between 2021 and 2025 from major academic databases. Thematic analysis was applied to synthesize key concepts related to human-centric smart manufacturing, human–robot collaboration, cyber-physical systems, digital twins, and sustainability performance indicators. The findings indicate that collaborative human–machine architectures enhance operational efficiency, quality consistency, adaptability, and resilience, while also supporting worker well-being, skill development, and environmental performance. However, gaps remain regarding long-term empirical validation, standardized sustainability measurement frameworks, and implementation in diverse industrial contexts. In conclusion, Industry 5.0 provides an integrative socio-technical framework in which human–machine collaboration functions as a strategic bridge between productivity enhancement and sustainable manufacturing performance.